Relations of glutamate carboxypeptidase II (GCPII) polymorphisms to folate and homocysteine concentrations and to scores of cognition, anxiety, and depression in a homogeneous Norwegian population: the Hordaland Homocysteine Study. - Halsted, C; Wong, D; Peerson, J; Warden, C; Refsum, H; Smith, A; Nygård, O; Ueland, P; Vollset, SE; Tell, G (2007)
BACKGROUND: Glutamate carboxypeptidase II (GCPII) encodes for intestinal folate hydrolase and brain N-acetylated alpha-linked acidic dipeptidase. Previous studies provided conflicting results on the effect of the GCPII 1561C-->T polymorphism on folate and total homocysteine (tHcy) concentrations. OBJECTIVE: We aimed to determine the potential effects of 2 polymorphisms of GCPII on plasma folate and tHcy concentrations, cognition, anxiety, and depression in a large aging cohort of Norwegians enrolled in the Hordaland Homocysteine Study. DESIGN: DNA samples were genotyped for the GCPII 1561C-->T and 484A-->G polymorphisms, and the results were linked to plasma folate and tHcy concentrations and to scores for cognition, anxiety, and depression. RESULTS: The 2 polymorphisms were in linkage disequilibrium and were associated with concentrations of tHcy. After adjustment for covariates, persons in the CT or combined CT and TT groups of the 1561C-->T polymorphism had higher plasma folate concentrations and lower tHcy concentrations than did those in the CC group. Subjects with the TT genotype had lower Symbol Digit Modalities Test (SDMT) scores than did subjects with the CC genotype. Compared with abstainers, moderate alcohol drinkers had higher plasma folate concentrations and higher scores on the Mini Mental State Examination. However, women abstainers with the CT genotype had lower SDMT scores than did abstainers with the CC genotype or moderate drinkers with the CT genotype. CONCLUSIONS: The 1561C-->T polymorphism is associated with higher plasma folate and lower tHcy concentrations and with lower SDMT cognitive scores in women who abstain from alcohol.